Optimización del sistema de vapor del plantel de refinería RECOPE S.A. Moín, Limón - Umaña López, Cindy Alejandra (Instituto Tecnológico de Costa Rica, 2011)
This work was developed for Refinadora Costarricense de Petróleo (RECOPE S.A.) Costa Rica’s oil company that, according to Law N˚7356, handles the import, refining and distributing of crude oil and its derivatives to meet domestic demand. The project's main objective is to contribute to the efficient use of steam on site in order to minimize the impacts it causes on the environment. For this project data was collected, about the configuration and operation of the steam system in the refinery, working side by side with the refining processes department, with was also consulted to determine options for improvement that were economically and environmentally viable. The main results of this project are the implementation of energy efficiency indicators to monitor steam generation and creation of manual for the maintenance of the steam area. These tools will enable systematic control of steam generation and distribution. In addition, this project concludes with the design of a condensate recovery system for the heating of heavy products area, generating savings close to $ 440.727,00 per year, with a recovery of investment period of 0.9 years. This will also reduce fuel consumption by 683 tons per year, which implies a reduction of 2.281 tons of CO2 emissions annually and facilitate the reduction of freshwater consumption by 108.950 m3 per year.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica. Escuela de Química, 2011.
Keywords: Presión; Asfalto; Rendimiento energético; Consumo de energía; Trampas; Viabilidad; Beneficios